Application of the methodology based on projects in university teaching: Case study in the audiovisual communication degree - Mora de la Torre, Victoria; Díaz-Lucena, Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The Spanish university system permits opportunities for improvement in its current study plans, since the incorporation of new technologies, together with educational innovations, are driving higher education towards significant changes. This proposal aims to account the case study where an experiential model based on projects is implemented in the subject: Production of Live News programmes on television. Consequently, after the evaluation of this training proposal where more than two hundred and fifty students have participated, it has been determined that it could be a valid and transcendent alternative to be applied in future academic courses.